2013
DOI: 10.1002/asia.201201063
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds against Alzheimer’s Disease: Molecular Recognition of Aβ1–42 Peptide by Salvia sclareoides Extract and its Major Component, Rosmarinic Acid, as Investigated by NMR

Abstract: Amyloid peptides, Aβ1-40 and Aβ1-42, represent major molecular targets to develop potential drugs and diagnostic tools for Alzheimer's Disease (AD). In fact, oligomeric and fibrillar aggregates generated by these peptides are amongst the principal components of amyloid plaques found post mortem in patients suffering from AD. Rosmarinic acid has been demonstrated to be effective in preventing the aggregation of amyloid peptides in vitro and to delay the progression of the disease in animal models. Nevertheless,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 66 publications
2
61
0
1
Order By: Relevance
“…42 The normalized signal strengths (STD/STD reference) corresponding to each ligand atom are proportional to its proximity to the amyloid fibril, allowing an atomic-level map of the binding interactions from the ligand to the Aβ fibril to be made. 12 p ,41 The results from the STD NMR experiments indicate that both 1 and 4 interact fairly strongly (mM to μM dissociation constant) with the fibril to elicit a relatively strong STD signal (approximately 4.5% (for 1 ) and 5.9% (for 4 ) of the reference signal at a 3 sec saturation power of 50 dB, similar in magnitude to previous results with other catechols 41 ). The STD results also suggest that 1 and 4 bind similarly to the Aβ fibril (Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…42 The normalized signal strengths (STD/STD reference) corresponding to each ligand atom are proportional to its proximity to the amyloid fibril, allowing an atomic-level map of the binding interactions from the ligand to the Aβ fibril to be made. 12 p ,41 The results from the STD NMR experiments indicate that both 1 and 4 interact fairly strongly (mM to μM dissociation constant) with the fibril to elicit a relatively strong STD signal (approximately 4.5% (for 1 ) and 5.9% (for 4 ) of the reference signal at a 3 sec saturation power of 50 dB, similar in magnitude to previous results with other catechols 41 ). The STD results also suggest that 1 and 4 bind similarly to the Aβ fibril (Fig.…”
Section: Resultssupporting
confidence: 85%
“…To probe these possible interactions, we employed saturation transfer difference (STD) NMR experiments to map the regions of the ligand which bind preformed fibrils of Aβ 40 (Fig. 8) 12 p ,41 and to visualize the potential contacts of 4 with Aβ fibrils, flexible ligand docking studies were employed with the solid state NMR structure of metal-free Aβ 40 (PDB 2LMN and 2LMO) (Figs. 8c, S9, and S10).…”
Section: Resultsmentioning
confidence: 99%
“…STD experiments were acquired with a train of 60 dB Gaussian-shaped pulses of 50 ms duration at centered at either −2.0 ppm (on resonance 6365 ) or 100 ppm (off resonance) with a total saturation time of 3 s on a Bruker 500 MHz (metal-free samples) or 900 MHz spectrometer (Zn( ii ) samples). 66 A total of 2048 transients with a 2 s recycle delay were collected for all spectra. Chemical shifts are referenced to water due to the potential interaction of Aβ40 with the chemical shift standard sodium 4,4-dimethyl-4-silapentane-1-sulfonate (DSS).…”
Section: Methodsmentioning
confidence: 99%
“…18,19 Among these, small organic molecules have received special interest because of their high permeability through the blood-brain barrier and potentially low cytotoxicity. 20 Several natural compounds have been found to prevent hIAPP brillization or to transform the mature brils into unstructured, off-pathway aggregates. 8,21,22 For example, Chen et al 23 have found that the brillation and aggregation of hIAPP is affected by trehalose in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%